Discontinuities and Post-Bureaucratic Organizing: A Framework and Research Propositions - Chudoba, Katherine M.; Kevin Crowston; Mary Beth Watson-Manheim (Academy of Management Conference, 2002)
Some organization theorists argue that prevailing theories of organizing are based primarily on detailed observations of bureaucratic work, but that the nature of work today is sufficiently different to bring the applicability of these theories into question. They note in particular the growth in white collar and service workers, the rise of contingent work and the increased application of computer technologies. While various kinds of non-bureaucratic work such as project-based work and non-traditional employees such as contractors is not new, the pace and intensity of work enabled by communications technologies suggest that a postbureaucratic theory of work may be appropriate. Indeed, virtual has become shorthand for novel work arrangements involving telecommuters or virtual organizations. We propose that an increasingly important characteristic of non-bureaucratic work settings is the fact that the workers in these environments face discontinuities, that is, a lack of coherence in aspects of their work, such as the work setting, task, relations with other workers or managers. In this paper, we argue that studying how discontinuities have been managed in a variety of settings may offer insights into the nature of post-bureaucratic work. The first contribution of this paper is a framework that illuminates commonalties in diverse non-bureaucratic work settings and thus suggests how the existing research in these settings might be integrated. Based on this framework, we then consider how various existing theories might be integrated into a theory of post-bureaucratic organizing. We conclude by proposing a set of questions for future research based on this perspective.
Keywords: Discontinuity; Virtuality